Isolation and characterization of heavy metal resistant psychrotrophs from antarctica - Yap, Mui Lan (2016)
The present study reported the isolation and characterisation of heavy metal resistant bacteria from Antarctic water. Ten isolates were successfully isolated from seawater and ice lower glacier and two isolates named SW5 and ILG1 were selected for further study based on their high resistance towards heavy metals particularly, arsenite and arsenate. Both isolates have optimum growth at 20°C to 30°C. Isolates SW5 and ILG1 were tested for their resistance to metal ions such as Cd(II), Cr(VI), As(III) and As(V) at different range of concentration namely, Cd(II) 3-30 ppm; Cr(VI) 15-135 ppm; As(III) 150-1500 ppm; and As(V) 150-7500 ppm. The minimal inhibitory concentration (MIC) of four heavy metals was determined in Low Phosphate Mediumfor each bacterial strain. The results of the test revealed that MIC for isolate SW5 was at 15 ppm, 30 ppm, 900 ppm and 7500 ppm for Cr(VI), Cd(II), As (III) and As(V) respectively while for ILG1, MIC was at 12 ppm for Cr(VI), 9 ppm for Cd(II), 750 ppm for As(III) and 3000 ppm for As(V). Overall, the order of toxicity of heavy metals to SW5 was in order of Cr(VI)> Cd(II)> As(III)> As(V) and for ILG1 was in order of Cd(II)> Cr(VI)> As(III)> As(V). Molecular characterization, 16S rRNA analysis revealed that isolate SW5 shares a 99.65% identity match to Pseudomonas azotoformans strain IAM 1603 while isolate ILG1 shares a 99.51% identity match to Pseudomonas cedrina subsp cedrina strain CFML 96-198. These bacteria could be used as a model microbial strain to study the mechanism of heavy metal resistance with potential application for bioremediation of heavy metals.